Editors’ Introduction to the Special Issue on "MATCOS-16 conference" - Brodnik, Andrej; Galambos, Gábor (Informatica, 2019)
This is an editorial to the Middle-European Conference on Applied Theoretical Computer Science (MATCOS-16) special issue.